THE DEVELOPMENT OF MATHEMATICS MODULE OF QUADRILATERAL AND TRIANGULAR BASED ON PROJECT-BASED LEARNING MODEL - Siska Audhina Kusumaningtyas; Suparman Suparman (Universitas Ahmad Dahlan, 2019)
Learning media is a set of information that is necessary for the implementation of learning. Teachers and students in need of additional media materials in the form of modules to facilitate delivering quadrilateral and triangular, besides the varied learning model, add to the range of learning processes with a level of understanding. This research aims to develop learning modules media math subject quadrilateral, and triangular-based model of learning project-based learning for students of Junior High School grades VII and find out the feasibility of modules in terms of material and media and knowing the student response against the math module. This type of research is research development. This study used Research and Development to identify the Potential and problems, collect information, design products, validate product design, product design, revisions to the test stage, try the product, product revisions, and test the product. This research is the State Junior High School (SMPN) 4 Wonosari and Junior High School (SMP) Muhammadiyah 1 Wonosari students. The type of data used, namely, data qualitative and quantitative data. They are using data collection techniques interviews and are now conducted before product development. The research instrument used is a question form and interview guidelines to assess the modules developed—the data analysis technique using quantitative analysis, which is then converted into the qualitative Likert scale analysis. Based on the research results obtained from the expert assessment of the material with an average score of 103.33 belongs in the category of excellent, expert assessment of the media with an average score of 109.33 belong in the category, and the response of the students against the module with an average score of 112.49 belong in the category. Based on the research of expert material, media experts, and student response towards developing the media learning modules on the subject of quadrilateral and triangular-based model of learning project-based learning for students of Junior High School grades VII feasibility in the learning process.